1986
DOI: 10.1002/ajh.2830220407
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of bone marrow aspirate particle smears, biopsy imprints, and biopsy sections

Abstract: Bone marrow aspirate particle smears, biopsy imprints, and biopsy sections were compared to determine the accuracy of the three samples in assessing for overall cellularity, differential cell count, megakaryocyte density, iron stores, and tumor infiltration. Aspirate particle smears and biopsy imprints were stained by Wright-Giemsa method. Aspirate particle smears were also stained with Prussian-blue. Biopsy sections were 1 1/2-2 micron thick and were prepared from non-decalcified plastic embedded samples and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 9 publications
(10 reference statements)
3
21
1
Order By: Relevance
“…Many studies done previously showed that BMB was a better procedure for detecting metastatic tumour. [7][8][9], Only 50% cases showed a positive correlation in our study, which is in agreement with studies by Atac et al [10] where he studied 39 cases and each positive BMB was also positive by BMA. In our study the metastasis were mostly adenocarcinomas 3/6 (primary from gastric carcinoma), 1/6 small cell carcinoma where the primary was unidentified, 2/6 cases of poorly differentiated carcinoma.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Many studies done previously showed that BMB was a better procedure for detecting metastatic tumour. [7][8][9], Only 50% cases showed a positive correlation in our study, which is in agreement with studies by Atac et al [10] where he studied 39 cases and each positive BMB was also positive by BMA. In our study the metastasis were mostly adenocarcinomas 3/6 (primary from gastric carcinoma), 1/6 small cell carcinoma where the primary was unidentified, 2/6 cases of poorly differentiated carcinoma.…”
Section: Discussionsupporting
confidence: 82%
“…Granulomatous change may be specific or non specific. [8,14] Though AFB stain was not positive in all the cases, the previous clinical history, presentation and other investigations helped us to clinch the diagnosis of a tuberculous granuloma. BMB is a better procedure for detecting granulomas in the marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Biopsy imprints were made by gently touching the core on slides. The cores were then fixed in 10% formalin (23) and decalcified in RDO Gold (Apex Engineering Products Corp., Aurora, IL). The specimens were embedded in paraffin and cut at 6 m.…”
Section: Methodsmentioning
confidence: 99%
“…It may also play an important role in the assessment of patient with pyrexia of unknown origin (PUO) as well as in the diagnosis of various storage and infiltrative disorders. (5) Bone marrow examination usually involves two separate but interrelated specimen i.e. bone marrow aspiration and needle biopsy of bone and associated marrow.…”
Section: Introductionmentioning
confidence: 99%